Verbal labels increase the salience of novel objects for preschoolers with typical development and Williams syndrome, but not in autism - Vivanti, Giacomo (J Neurodev Disord, 2016)
BACKGROUND: Early research has documented that young children show an increased interest toward objects that are verbally labeled by an adult, compared to objects that are presented without a label. It is unclear whether the same phenomenon occurs in neurodevelopmental disorders affecting social development, such as autism spectrum disorder (ASD) and Williams syndrome (WS). METHODS: The present study used a novel eye-tracking paradigm to determine whether hearing a verbal label increases the salience of novel objects in 35 preschoolers with ASD, 18 preschoolers with WS, and 20 typically developing peers. RESULTS: We found that typically developing children and those with WS, but not those with ASD, spent significantly more time looking at objects that are verbally labeled by an adult, compared to objects that are presented without a label. CONCLUSIONS: In children without ASD, information accompanied by the speaker’s verbal label is accorded a “special status,” and it is more likely to be attended to. In contrast, children with ASD do not appear to attribute a special salience to labeled objects compared to non-labeled objects. This result is consistent with the notion that reduced responsivity to pedagogical cues hinders social learning in young children with ASD.